2023
DOI: 10.1002/eat.23901
|View full text |Cite
|
Sign up to set email alerts
|

Divergent trajectories of positive affect following maladaptive and non‐maladaptive exercise among individuals with binge‐spectrum eating disorders

Abstract: Objective: Individuals with eating disorders (EDs) often engage in maladaptive exercise (e.g., feeling driven, or to "compensate" for eating) which maintains eating pathology.Maladaptive exercise has been theorized to help individuals with EDs regulate emotions by enhancing positive affect (PA) and reducing negative affect (NA) associated with binge episodes and poor body image. However, no research has considered the presence of non-maladaptive exercise or evaluated this theory in binge-spectrum EDs.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…These findings add to previous literature, which has considered affect and fear of weight gain as independent risk‐factors for maladaptive exercise. For example, one recent EMA investigation found no predictable pattern of NA before or after exercise and only an initial increase in PA, followed by a plateau, closer to both adaptive and maladaptive exercise episodes (Lampe et al., 2023). Another study found that increases in fear of weight gain at one survey did not significantly predict any exercise engagement by the next survey (Lampe et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings add to previous literature, which has considered affect and fear of weight gain as independent risk‐factors for maladaptive exercise. For example, one recent EMA investigation found no predictable pattern of NA before or after exercise and only an initial increase in PA, followed by a plateau, closer to both adaptive and maladaptive exercise episodes (Lampe et al., 2023). Another study found that increases in fear of weight gain at one survey did not significantly predict any exercise engagement by the next survey (Lampe et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Fifty‐eight participants in the current analysis were included in other published studies examining associations between exercise engagement and body dissatisfaction (Srivastava et al., 2022), and fear of weight gain (Lampe et al., 2022) and examining reasons for exercise engagement (Lampe, Trainor, et al., 2021). All participants in the current analysis were also included in a published study examining trajectories of positive and NA around exercise episodes (Lampe et al., 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated 11 full scales assessing maladaptive exercise in populations with eating pathology as well as commonly sourced exercise items from four scales assessing general eating pathology (see Table 1); sources were selected from those used in ED samples, and included in recent reviews and chapters (Lampe & Gorrell, 2023;Rizk et al, 2020). Instruments were included based on their frequency in the literature, appearance in studies comparing multiple scales, and citation count based on a consensus among the seven authors.…”
Section: Identification Of Instrumentsmentioning
confidence: 99%
“…Fifth, the modified EDE questions assessing frequency of compensatory‐only, compulsive‐only, and both compulsive and compensatory exercise have not been independently validated. Previous studies using ecological momentary assessment (EMA) have demonstrated that 94.44% of individuals who endorse these modified exercise items also reported at least one episode of EMA‐measured compensatory and/or compulsive exercise engagement over the following 7–14 days (Lampe et al, 2023). In this study, the correlation between assessment of exercise via modified EDE items and EMA was r = .49 ( p < .001).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%